Pemesanan dan Penjualan Kue Berbasis Android pada Chérie Cake’s – Halim Perdana Kusuma - Siswantoro, Yostyo; Hasti, Novrini (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
Cherie Cake's is a business that runs on the ordering and selling of cookies and cakes. The process of promotion, ordering, and selling are still manually, which buyers have to come to the place of business cake. Making a mobile-based application is designed to make it easier for consumers to order products because it only needs to choose the available products which also listed the price of each product. For the total price of the order, will also be displayed properly and can be determined quickly without waiting for a reply from the seller.